REPRESENTATION OF POWER AND IDEOLOGY ON JOKOWI'S SPEECH - Haryo Sutanto; Dwi Purbaningrum (Universitas Prof. Dr. Moestopo (Beragama), 2022)
A speech reflects the power and ideology of the communicator when it is delivered. It also has the representation of the social and political situation at the time it is delivered. The speech is about the successful handling of the Covid-19 Pandemic and the initial success of economic recovery among ASEAN countries. This research intends to open a new understanding of a speech discourse. A speech discourse can carry many meanings that are packaged in the representation of the power and ideology of the communicator. Having the ability to read the meaning behind a speech is an advance in building a civil society. The representation were analyzed through three level of analysis of critical discourse analysis. The first is to analyze text with features associated with the text as-a-whole, the second is to analyze text with features related to text at the sentence level and word level, and the third is to analyze the findings through contextual interpretation. The result of this speech analysis shows that Jokowi’s speech has represented the power of Indonesia as the next leader of ASEAN Chair in 2023 and the ideology of Indonesia to develop together with other Southeast Asia countries in ASEAN.